Musculoskeletal Complications of Juvenile Idiopathic Arthritis in a Tertiary Care Hospital Peshawar - Mian Saleem Shah; Syed Ahmad Shah; Aizaz Afridi; Manzoor Ali Khan; Jamil Ahmed Kiyani; Nayab Sarwar (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: The objective of this retrospective cross-sectional research was to examine the musculoskeletal problems associated with Juvenile Idiopathic Arthritis (JIA) at a tertiary care hospital located in Peshawar, Pakistan, during the period spanning from March 2022 to March 2023 Methods: The study included the collection and analysis of data from patients with Juvenile Idiopathic Arthritis (JIA) who were undergoing treatment at the hospital. Descriptive statistics, subgroup analyses, and Fisher's Exact test were used to investigate potential connections between JIA and musculoskeletal problems. . Results: The analysis revealed a range of demographic features, with a significant proportion of pa- tients (52.9) falling between the age range of 11-15 years. The most common subtype of JIA was Polyarticular RF Negative, accounting for 44.1 of cases. This subtype was characterized by high lev- els of Erythrocyte Sedimentation Rate (ESR) (64.7) and C-reactive protein (CRP) (47.1), which are indicative of inflammation. The study revealed statistically significant correlations between substantial joint involvement, swelling, and discomfort in individuals with musculoskeletal conditions (p 0.05). Nevertheless, the health evaluations conducted by patients and parents did not reveal any significant association with musculoskeletal issues. Significant correlations were seen between a positive fam- ily history of JIA or other RMDS and musculoskeletal disorders (p 0.05). Conclusion: The present research emphasizes the need to conduct a thorough medical history and physical tests for diagnosing Juvenile Idiopathic Arthritis (JIA), with a special focus on children who have distinct symptoms. Providing healthcare personnel with knowledge about musculoskeletal com- plaints may assist in promptly identifying and treating them, therefore enhancing patient results.